The Relationship Between Students’ Attitudes Towards Cooperative Learning Strategies and Their Academic Achievement - Nou, Hanrith; Mok, Sarom; Lim, Sothea; Em, Sereyrath (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the Study: The purpose of this study was to investigate students’ attitudes toward cooperative learning, their levels of academic achievement, the relationship between these two dimensions, and the reasons behind their demonstrated attitudes. Methodology: This explanatory sequential mixed methods design was employed, and the convenient sampling technique was adopted to choose 422 students and 7 teachers studying and working at two Generation Schools (NGSs). A survey questionnaire and interview protocol were utilized to collect the data. The statistics, such as percentage, mean, standard deviation, and the independent samples t-test, were used to analyze the data. Main Findings: The findings indicated that students’ attitudes towards cooperative learning were highly positive. The reason behind students’ attitudes towards cooperative learning focuses on its value and benefits. That is to say, students valued cooperative learning for its benefits, including the development of social skills and cognitive domain, stress reduction, enjoyment, and learning performance. However, they had some concerns, including time-consuming, conflicting interests, and potential grade drawbacks in terms of their final course grade. Novelty/Originality of this study: The study revealed that cooperative learning improves social skills, cognitive growth, and stress reduction, but students are also concerned about efficiency and fairness in grading. Accordingly, this study shed light on the practical and emotional problems of cooperative learning that were generally missed in the literature. The findings would also provide a more complete knowledge of cooperative learning's adoption in education by bridging theoretical advantages and real-world student concerns.